The EU’s (Un)Common Visa Policy: Lost in Aspirations - Mananashvili, Sergo (2014)
Initially developed as a flanking measure to external border controls, necessary for an area without internal borders, the EU's common visa policy has been gradually gaining new dimensions. It is no longer considered a mere instrument of "policing at a distance", contributing to the prevention of irregular immigration.